Association between low birth weight and impaired glucose tolerance in children: a systematic review and meta-analysis - Ma, Jun; Wang, Youfang; Mo, Mengyan; Lian, Zerong (Frontiers in Pediatrics, 2024)
Background: A potential association between the onset of diabetes and normal birth weight (NBW) has been discovered. Diverse conclusions and study methodologies exist regarding the connection between low birth weight (LBW) and impaired glucose tolerance in children, underscoring the need for further robust research. Our institution is embarking on this study to thoroughly examine the association between LBW and impaired glucose tolerance in children.We conducted searches on Cochrane Library, ScienceDirect, EMBASE, PubMed, China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature data (CBM) online database, VIP full-text Database, and Wanfang Database to identify correlation analyses or case-control studies investigating the relationship between LBW and abnormal glucose tolerance in children. The search spanned from January 2010 to September 2023. The quality of observational studies was evaluated using the Newcastle-Ottawa Scale (NOS) tool. Data synthesis was performed using the statistical software RevMan 5.3 for meta-analysis.Results: Based on the preferred reporting items for systematic reviews and metaanalysis (PRISMA) guidelines, we finally included 10 clinical control studies consisting of a total of 2971 cases. There wasn't considerably change in blood sugar levels among LBW, NBW and high birth weight (HBW) infants (P>0.05). There was no significant difference in insulin levels between LBW infants and NBW infants (P>0.05). The HOMA-IR of LBW infants was considerably higher than that of NBW infants (P<0.05). The risk of abnormal glucose tolerance in LBW infants was 0.42 times higher than that in NBW and HBW infants [Fisher's Z = 0.42, 95% CI = (0.09,0.75), P=0.01].LBW is associated with an increased risk of abnormal glucose tolerance, as indicated by elevated HOMA-IR level in LBW infants compared to NBW and HBW pediatric population. Further research is needed to confirm and expand upon these findings to better understand the complex relationship between LBW and impaired glucose tolerance in children.